Community Awareness and Perception about Museums to make them Tourist-Friendly Destinations: A Case Study of District Peshawar - Anas Mahmud Arif; Naveed Usman; Waheed Alam (Journal of Management Practices, Humanities and Social Sciences, 2021)
The museum plays a key role in preserving the cultural heritage and is a source of education for the community in connection with it. The linkage of community with its heritage is evidence of their interest and attraction towards the activities of their ancestors. The community that is keenly interested in delivering their cultural assets to the upcoming generations always takes the museum-community linkage seriously. The study deals with assessing the museum-community relationships targeting the male and female students and teachers of the primary level at District Peshawar. In this study, the requisite data was retrieved using the questionnaire. The questionnaire was designed after the careful study of several kinds of research in the